DETERMINASI DALAM KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH - Sahala Purba; Rasdianta Purba (Jurnal Akuntansi Trisakti, 2023)
This study aims to understand and analyze the impact of accounting knowledge, government internal management systems, the use of information technology, and the internal audit function. This research uses primary data using a questionnaire to gather the data. This research was conducted in Regional Apparatus Organizations throughout Deli Serdang Regency. The respondents in this study were 69 people. The results of this study found that accounting knowledge, government internal management systems, and the use of information technology have a positive impact on the quality of local government financial reports, while the internal audit function has a negative impact on the quality of local government financial information. The implication of this research is that having good accounting knowledge is supported by a strong government internal management system, and the use of information technology and the existence of an optimal internal audit function will be able to increase the quality of local government financial information in all local governments in Indonesia, especially in districts Deli Serdang.